2021
DOI: 10.1177/09544062211047844
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion, optimization and surface analysis of Fe-Al2O3-CeO2 metal matrix nanocomposites

Abstract: In the present work, metal matrix nanocomposites are being prepared using Fe as base material reinforced with Al2O3 and doped with CeO2. Nanocomposite specimens were synthesized using powder metallurgy technique. Tafel Polarization, Corrosion Behavior and its optimization using Analysis of Variance (ANOVA) as well as Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) along with Phase and Microstructure of prepared samples have been investigated. It was observed that corrosion rate and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The paper [22] presents the results of research on the effect of catholyte on the kinetics of corrosion was studied and revealed the dependence of the corrosion rate of carbon steel 09G2S on the concentration of the reagent alkali and catholyte at different pH values where a comparative assessment of the use of the most effective concentration of catholyte to increase the corrosion resistance of the material has been carried out. The paper [23] presents the results of research on the preparation of metal matrix nanocomposites using Fe as base material reinforced with Al 2 O 3 and doped with CeO 2 using the powder metallurgy technique. It was observed that corrosion rate and corrosion current density was highest for pure Fe samples whereas 1.0 % CeO 2 doped Fe-Al 2 O 3 metal matrix nanocomposite system showed the formation of nano amorphous layer on the specimen surface.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The paper [22] presents the results of research on the effect of catholyte on the kinetics of corrosion was studied and revealed the dependence of the corrosion rate of carbon steel 09G2S on the concentration of the reagent alkali and catholyte at different pH values where a comparative assessment of the use of the most effective concentration of catholyte to increase the corrosion resistance of the material has been carried out. The paper [23] presents the results of research on the preparation of metal matrix nanocomposites using Fe as base material reinforced with Al 2 O 3 and doped with CeO 2 using the powder metallurgy technique. It was observed that corrosion rate and corrosion current density was highest for pure Fe samples whereas 1.0 % CeO 2 doped Fe-Al 2 O 3 metal matrix nanocomposite system showed the formation of nano amorphous layer on the specimen surface.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%